Elements. - Farrow, Nick; Roberts, Paul (Environmental studies in video, 2002)
Earth- Animal activists: In favour of a vegetarian Kenya. Water- Arctic Circle: The annual dogsled race. Cause And Effect- Foot and Mouth scare reaches European zoos. Earth- Heibei Province: Land lies abandoned. Earth- Wyoming Yellowstone National Park: Worst forest Fire in one hundred years. And Finally- Southeast Asia: Logging will lead to the extinction of the orangutan.